Pengaruh Kepuasan Komunikasi terhadap Motivasi Kerja Karyawan pada PD BPR Bank Pasar Bogor - Taufiq Azhary Siregar; Aida Vitayala S Hubeis; Nurmala Katrina Pandjaitan (Institut Pertanian Bogor, 2015)
Communication is organized coordination between various subsystems within the organization. High employee communication satisfaction individually will drive the performance of human resources as a whole and provide the right feedback on behavior change, which is reflected in the increase in productivity. In 2013 the closing happened many BPR in various areas, namely ninth BPR, one of which is in the city of bogor. This study examined the influence of communication satisfaction regarding how to employee motivation. The object of the research taken are all employees in PD BPR Bank Pasar Bogor Bogor. The methods used in this study using the method of survey which the total number of respondents there were 43 peoples. Method of processing data using descriptive and statistical analysis using Partial Least Squares (PLS) using SmartPLS 2.0. Based on theresults of the analysis satisfaction of communication influence on employee motivation, the value of R-square on the research is 0.6121 percent, which means that the exsogen variable (satisfaction of communication) are able to explain the diversity of the endogen variable (motivation) by 61.21%, also significant effects between variable communication satisfaction of work motivation.